Change in risk factors for coronary heart disease during 10 years of a community intervention programme (North Karelia project). Issue 6408 (17th December 1983) - Puska, P; Salonen, J T; Nissinen, A; Tuomilehto, J; Vartiainen, E; Korhonen, H; Tanskanen, A; Rönnqvist, P; Koskela, K; Huttunen, J
Abstract : A comprehensive community based programme to control cardiovascular diseases was started in North Karelia, Finland, in 1972. Reductions in smoking, serum cholesterol concentrations, and blood pressure were among the central intermediate objectives. The effect of the programme during the 10 year period 1972-82 was evaluated by examining independent random population samples at the outset (1972) and five (1977) and 10 (1982) years later both in the programme and in a matched reference area. Over 10 000 subjects were studied in 1972 and 1977 (participation rate about 90%) and roughly 8000 subjects in 1982 (participation rate about 80%). Analyses were conducted of the estimated effect of the programme on the risk factor population means by comparing the baseline and five year and 10 year follow up results in the age range 30-59 years. The effect of the programme (net reduction in North Karelia) at 10 years among the middle aged male population was estimated to be a 28% reduction in smoking (p less than 0.001), a 3% reduction in mean serum cholesterol concentration (p less than 0.001), a 3% fall in mean systolic blood pressure (p less than 0.001), and a 1% fall in mean diastolic blood pressure (p less than 0.05). Among the female population the reductions were respectively, 14% (NS), 1% (NS), 5% (p less than 0.001), and 2% (p less than 0.05). During the first five years of the project (1972-7) the programme effectively reduced the population mean values of the major coronary risk factors. At 10 years the effects had persisted for serum cholesterol concentrations and blood pressure and were increased for smoking.